Presacral Tumor: Insights From a Decade’s Experience of This Rare and Diverse Disease - Li, Zeyu; Lu, Min (Frontiers in Oncology, 2021)
Background: Presacral tumors are a group of rare and heterogeneous tumors that arise from the potential presacral space between the rectum and sacrum. The low occurrence and diverse origins make the diagnosis and treatment of these tumors a challenge. The aim of the study was to retrospectively review patient demographics and to identify advantages and disadvantages in the diagnosis and treatment of these tumors. Methods: Retrospectively collected and reviewed data from patients who received treatment of presacral tumors at the First Affiliated Hospital of China Medical University between August 2009 and June 2019. Results: The data from forty-four patients (33 females) with a median age of 50 years who were diagnosed with a presacral/retrorectal tumor were analyzed. The majority of tumors were congenital (61.4%) and benign tumors are more common (59.1%). The median age of patients with benign tumor was significantly higher than that of malignant tumor. The most common symptoms were sacrococcygeal /perianal pain (56.8%) and mass (36.4%), and 8 out of 9 patients having lower limb symptoms diagnosed with malignant tumor. The tumor detection rate of digital rectal examination was 75% and more than 90% of all patients underwent one or more radiology imaging exams for tumor diagnosis. Every patient had a biopsy result. The most common type of tumor was presacral cyst (40.9%) with overall tumor median size of 5.6 cm. Thirty-one (70.5%) patients underwent surgery, most often via the posterior route (83.9%). Posterior route surgery had significantly shorter operation time and tumors operated via posterior route were significantly smaller. The survival rate after surgery was 100%. The median course of disease was 6 months and median follow-up was 25 months. Conclusions: Presacral tumors have low occurrence and are more frequently observed in females in their 30s and 50s indicating a possible link between tumor occurrence and hormonal changes. Patients with lower limb symptoms were more likely to have a malignant presacral tumor. Posterior route was the most commonly utilized surgical approach. Supplementary iodine tincture treatment of cysts ruptured in operation could potentially be helpful in reducing the chance of recurrence.